(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
DIKSHA (Digital Infrastructure for Knowledge Sharing) is a national platform for school education. Under the PM e-Vidya initiative of the Government of India, which was declared as part of the Atma Nirbhar Bharat, DIKSHA has been declared as ‘One Nation, One Digital Platform’ as it is built on open-source technology. Present study addresses the following questions- What is the awareness and utilization status of the DIKSHA online teaching-learning platform among students at the secondary stage in Varanasi City? Does the awareness of the DIKSHA online teaching learning platform correlate with its utilization among students studying at the secondary stage in Varanasi City? A descriptive survey method was used to conduct the study. Self-constructed questionnaire entitled "Awareness and Utilization Questionnaire for DIKSHA Online Platform" was used to collect the data. Data obtained through field visits to sampled secondary schools of Varanasi city were analyzed in view of the objectives and hypotheses of the study. Descriptive statistics, group bar diagrams, percentages, and Student's t-test for independent samples were used in analyzing the data through SPSS and MS Excel software. Present study depicts that secondary stage students showed a low average level of awareness about the DIKSHA online teaching-learning platform, which shows that the students are less aware about the various aspects of instructional facilities provided on the DIKSHA platform. The study further showed that the utilization status of DIKSHA online teaching-learning platform at secondary stage is satisfactory. No significant difference was found in the awareness level of DIKSHA online teaching-learning platform among male and female students of secondary stage but there is a significant difference found in utilization status of male and female students about DIKSHA online teaching-learning platform. No significant difference was found in the awareness level of DIKSHA online teaching-learning platform among government and private school students but there is a significant difference found in the utilization status of DIKSHA online teaching-learning platform among government and private school students.